SHORE SEINES FOR RESERVOIRS - PART I- DESIGN AND PERFORMANCE - GEORGE, V C; KHAN, A A; VARGHESE, M D (Fishery Technology, 2017)
Based on the studies to introduce active gears in reservoirs, a prototype shore seine was designed and tested, the details of which are presented in this communication. The results revealed that the operation of this gear could effectively control the proliferation of under-exploited species.